The Influence Of Leadership Style And Communication On Employee Performance At RPA Jabal Nur Ciamis - Firdaus, Elanda Rachman; Barlian, Barin; Sutrisna, Arga (Utami Publisher, 2025)
This research aims to determine the influence of leadership and communication styles on employee performance at RPA Jabal Nur Ciamis. The method used was quantitative with a research sample of 54 employee respondents. The data used is primary data. The analytical tool used in this research is multiple linear regression using SPSS Version 25. The results of the research show that the Leadership Style perceived by RPA Jabal Nur Ciamis employees has very good criteria. The communication possessed by RPA Jabal Nur Ciamis employees has very good criteria. The performance of RPA Jabal Nur Ciamis employees has very good criteria. Simultaneously Leadership Style and Communication have a significant effect on Employee Performance. Partially Leadership and Communication Style have a significant effect on Employee Performance.